Encapsulation with the Protrusion of Cruciform 9, 10‐Bis(arylethynyl)anthracene Derivatives in a Self‐Assembled Boronic Ester Cavitand Capsule: Photochemical and Photophysical Properties. Issue 5 (25th February 2014) - Hirumi, Yohei; Tamaki, Kento; Namikawa, Tomotaka; Kamada, Kenji; Mitsui, Masaaki; Suzuki, Kengo; Kobayashi, Kenji
Abstract The self‐assembled boronic ester cavitand capsule 3 quantitatively and tightly encapsulates 2, 6‐diacetoxy‐9, 10‐bis(arylethynyl)anthracene derivatives 4 a–4 c as highly fluorescent cruciform guests to form complexes 4 a@3, 4 b@3, and 4 c@(3)2. The structural features of capsule 3, which possesses two polar bowl‐shaped aromatic cavity ends and four large equatorial windows connected by dynamic boronic ester bonds, made it possible to encapsulate cruciform 4 with protection of the reactive anthracene core inside the capsule and with two protruding arylethynyl groups, the π‐conjugated arms of compound 4, through two of the equatorial windows of the capsule. Thus, complexes 4 a@3, 4 b@3, and 4 c@(3)2 show greater resistance to photochemical reactions in solution and fluorescence quenching in the powder state compared to free guests 4. In addition to the improved photostability, restriction of the free rotation of the arylethynyl groups of guests 4 upon encapsulation results in sharpening of the UV/Vis absorption peaks with a red‐shift and a significant increase in some of the two‐photon‐absorption peaks of complexes 4 a@3, 4 b@3, and 4 c@(3)2 compared with free guests 4.